Factors associated with deep infiltrating endometriosis versus ovarian endometrioma in China: a subgroup analysis from the FEELING study - Yi Dai; Yingfang Zhou; Xinmei Zhang; Min Xue; Pengran Sun; Jinhua Leng; Charles Chapron (BMC, 2018)
Abstract Background To compare potential factors associated with deep infiltrating endometriosis (DIE) versus ovarian endometrioma (OMA) among endometriosis patients in China. Methods A subgroup analysis of factors associated with DIE versus OMA was performed in Chinese women from the FEELING study. This study included 156 OMA patients and 78 DIE patients. Retrospective information on symptoms and previous medical history was collected via face-to-face interviews; patients also completed a questionnaire to provide information on current habits. Univariate and multivariate logistic regression analyses were conducted to identify potential factors that are associated with DIE versus OMA. Results From univariate analysis, women who were married, at older age, had any siblings, prior pregnancy, or longer time since age at menarche on the day of visit were more likely to be diagnosed with DIE (P < 0.05). Also, the incidence of previous uterine surgery, menstrual and ovulatory disorders, deep dyspareunia, and gastrointestinal symptoms during menstruation were major factors that were significantly associated with the diagnosis of DIE (P < 0.05). Multivariate analysis showed that women with any siblings, gastrointestinal symptoms during menstruation, or eating a greater number of fruit/vegetables per day were more likely to be diagnosed with DIE. Meanwhile, eating organic food and experiencing stress were major factors that are associated with the diagnosis of OMA. Conclusions The findings provide additional information on the potential risk factors that are associated with DIE, compared with OMA among Chinese endometriosis patients. The results may help to better understand DIE versus OMA, and aid in earlier risk stratification and diagnosis of the patients. Trial registration NCT01351051. Registered 10 May 2011.